Spatio-temporal trends of seasonal climate parameters in the Western Himalayan Region - Chitra Kumar; Divya Mehta; Swapnil Rai (Environmental Monitoring and Assessment, 2026)

Ecosystem functioning across natural and managed Floodplain Forests of the Amazon Estuary: Implications for sustainable management - Divya Mehta; Ciro Abbud Righi; Marcelino Carneiro Guedes; Vinicius Gonçalves; João Luís Ferreira Batista (Forest Ecology and Management, 2026)

Genetic diversity studies in bell pepper (Capsicum annuum L. var. Grossum Sendt.) genotypes for growth, yield and quality traits - Divya Arti; D. K. Mehta; Shraddha Shraddha; Jyoti Singh; Nirankar Nirankar (Vegetos, 2025)

Systematic review on carbon and biodiversity in forest ecosystems of Amazonia - Divya Mehta; Ciro Abbud Righi; Chitra Kumar; Carlos Rodrigues Pereira (Environmental Monitoring and Assessment, 2025)

Allometric scaling and carbon sequestration in agroforestry species of the Western Himalayas: a model-based approach - Megha VR; R. Kaushal; Sadikul Islam; Uday Mandal; Harsh Mehta; Rajkumar; J. M. S. Tomar; Anand Kumar Gupta; Anupam Barh; Vishwal Madhav P; Vibha Singhal; Rajiv Pandey; et al. (Environmental Monitoring and Assessment, 2025)

Optimization of QuEChERS method for determination of pesticide residues in vegetables and health risk assessment - Sivaperumal Perumal; Divya Kottadiyil; Rupal Thasale; Tejal Mehta (Environmental Science and Pollution Research, 2024)

Genomic selection: a revolutionary approach for forest tree improvement in the wake of climate change - Umesh Sharma; H. P. Sankhyan; Anita Kumari; Shikha Thakur; Lalit Thakur; Divya Mehta; Sunny Sharma; Shilpa Sharma; Neeraj Sankhyan (Euphytica, 2024)

Prevalence of extended spectrum β-lactam, methicillin, and vancomycin resistant zoonotic bacterial pathogens in milk - Raghu Vishweswaraiah; Divya Sharma; Mehak Mehta; Avinash Jaswal; Kriti Dua; Rashmi Mallappa; Diwas Pradhan; A.S. Mariya Divanshi; Gurjinder Kaur; Naresh Kumar; Anil Kumar Puniya (Food and Humanity, 2023)

In Silico Screening as a Tool to Prepare Drug-Drug Cocrystals of Ibrutinib-Ketoconazole: a Strategy to Enhance Their Solubility Profiles and Oral Bioavailability - Divya Dhatri Kara; Pragathi Devanand Bangera; Chetan Hasmukh Mehta; Katikala Tanvi; Mahalaxmi Rathnanand (AAPS PharmSciTech, 2023)
Ibrutinib (IBR) is a biopharmaceutical classification system (BCS) class II drug and an irreversible Bruton’s tyrosine kinase (BTK) inhibitor. IBR has an extremely low oral bioavailability due to the activity of the CYP3A4 enzyme. The current intention of the research was to enhance solubility followed by oral bioavailability of IBR using the hot melt extrusion (HME) technique by formulating drug-drug cocrystals (DDCs). Ketoconazole (KET) is an active CYP3A4 inhibitor and was selected based on computational studies and solubility parameter prediction. Differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FT-IR), powder X-ray diffraction (PXRD), thermogravimetric analysis (TGA), proton nuclear magnetic resonance ( 1 H NMR), and scanning electron microscopy (SEM) evaluations were employed for estimating the formation of IBR-KET DDCs. The IBR-KET DDC system was discovered to have a hydrogen bond (H-bond) and π-π-stacking interactions, in accordance with the computational results. Further, IBR-KET DDCs showed enhanced solubility, stability, powder dissolution, in vitro release, and flow properties. Furthermore, IBR-KET-DDCs were associated with enhanced cytotoxic activity in K562-CCL-243 cancer cell lines when compared with IBR and KET alone. In vivo pharmacokinetic studies have shown an enhanced oral bioavailability of up to 4.30 folds of IBR and 2.31 folds of KET through IBR-KET-DDCs compared to that of the IBR and KET suspension alone. Thus, the prepared IBR-KET-DDCs using the HME technique stand as a favorable drug delivery system that augments the solubility and oral bioavailability of IBR along with KET. Graphical abstract

Determination of multi-class pesticide residues in food commodities from Gujarat, India and evaluation of acute and chronic health risk - Sivaperumal Perumal; Meghna Mahesh; Divya Kottadiyil; Tejal Mehta; Rupal Thasale (Environmental Science and Pollution Research, 2023)

Strategic Supplementation of Antioxidant Micronutrients in Peri-parturient Murrah Buffaloes Helps Augment the Udder Health and Milk Production - Himanshu Pratap Singh; Ravindra Kumar Jain; Divya Tiwari; Mukesh Kumar Mehta; Vishal Mudgal (Biological Trace Element Research, 2021)

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)